Urban regeneration of industrial heritage cities: A comparative study of textile manufacturing in Łódź (Poland) and Yazd (Iran) - Dehghan Pour Farashah, Mohammadhossein (European Spatial Research and Policy, 2026)
This study conducts a comparative analysis of the urban regeneration processes in Łódź, Poland, and Yazd, Iran. Despite the fact that both cities share a common historical background in textile manufacturing, they are characterised by distinct political, cultural, and socio-economic contexts. This research synthesises the findings of six doctoral papers to explore the values associated with textile manufacturing heritage, the role of post-industrial functions in urban management, and the determinants influencing urban regeneration. The methodology employed semi-structured interviews with stakeholders, complemented by fieldwork and observational analyses of textile manufacturing heritage sites, with a particular emphasis on revitalisation projects. While the Historic Urban Landscape framework examines the principles of spatial integration, the critical heritage studies approach evaluates the representation of heritage and the construction of meaning. By integrating comparative perspectives from Central European and Middle Eastern contexts, this research provides transferable strategies for policymakers, urban planners, and heritage managers aimed at fostering equitable, culturally informed, and sustainable urban transformation within industrial districts.